Time-dependent reliability analyses of prestressed concrete girders strengthened with CFRP laminates. (1st October 2019) - Dias-da-Costa, D.; Neves, L.A.C.; Gomes, S.; Hadigheh, S.A.; Fernandes, P.
Highlights: A time-dependent reliability analysis procedure is proposed for prestressed concrete girders. The girders are strengthened with CFRP after unacceptable levels of safety. Spatial and temporal effects of pitting corrosions and degradation of the CFRP are included. Ditlevsen bounds are proposed to correlate segments in spatial discretisation. Estimation of target reliability improves with the proposed approach. Abstract: This paper presents a time-dependent reliability analysis of prestressed concrete girders subjected to degradation caused by pitting corrosion. The procedure presented includes the effects of both spatial and temporal pitting corrosions on prestressing steel, as well as the degradation of the strengthening CFRP laminate used for the rehabilitation of the member. Results indicate that the correlation of corrosion in different segments of the prestressing tendons impacts on the computed safety index for the deteriorated structure. Ditlevsen bounds are proposed for a better approximation of the correlation between failure modes in the spatial discretisation. Results show that such approach produces adequate estimates of the reliability index over the full range of analysis in comparison with other tested models. It is also observed that the degradation of the CFRP laminates does not affect the reliability as significantly as corrosion, and that traffic loads, models uncertainties, corrosion error and corrosion rate are the most relevant variables in the analysis, followed by prestressing strength and concrete cover. The significance of the variables changes with time: the corrosion rate, corrosion model error and concrete cover increase in importance with the development of corrosion, whereas traffic loads become gradually less important.